Analysis of the Duration of High Winds During Landfalling Hurricanes - Kopp, Gregory A.; Li, Si Han; Hong, H. P. (Frontiers in Built Environment, 2021)
The duration of wind storms over a threshold wind speed value is known to be an important parameter in determining damage and losses, with losses tending to increase with the duration. This is because peak pressures tend to increase with longer duration, many building components and cladding systems are vulnerable to different types of fatigue mechanisms, and the yielding of linear elastic materials in the plastic range depends on the number of load cycles. A hurricane model was used to examine the duration of high winds in the United States at Miami, Galveston, and Charleston with the goal of establishing duration statistics for hurricanes as a function of peak wind speed. It was found that the duration of high winds, defined as the time that the 10-min wind speeds are within 30% of the peak 10-min wind speed, had a significant variation with a range from tens of minutes to more than 20 hrs, depending on location. The median duration ranged from 1.5 to 4 hours at the three locations, depending on location and the design wind speed level (i.e., the risk Category of the building). These results were used to establish a simple normalized model for wind speed as a function of time, which could be used together with the design wind speed to establish load cycles for design.